Perencanaan Sinyal Lalu Lintas Persimpangan Tiga Lengan Pada JL. Imam Bonjol – JL. Abdul Rahman Saleh Kota Pontianak - Azwansyah, Heri (Faculty of Engineering, Universitas Tanjungpura, 2017)
Abstract– This study aim to plan traffic light at intersection three arm of Imam Bonjol Street – Abdul Rahman Saleh Street in Pontianak City. This Study require data of intersection geometric and vehicle traffic obtained of field survey. This study yield planning of traffic light 3 phase with cycle time 160 second. Green time of actual for phase 1 (Street of Jl. Imam Bonjol (a)) equal to 66 second, for phase 2 (Street of Jl. Imam Bonjol (b)) equal to 63 second, and for phase 3 (Street of Abdul Rahman Saleh) equal to 10 second. Keywords- Traffic Light, Cycle Time, Green Time